(untitled) (Indian Journal of Animal Production and Management, 2016)
Welfare of the dairy cows is one of the major concerns in most of the developing countries due its impact on the productivity of cows, health of the animal, climate as well as on public health in the present day context. Consumers are increasingly more aware of the impact of dairy cow welfare on public health, dairy product safety and health propriety as well as environmental protection. As a result, to-day more and more consumers are oriented towards buying products from animals whose welfare is not threatened and where it is guaranteed that the products from farm animals are in the line with the standards of good husbandry practices in the farm.